ACL injuries in men's professional football: a 15-year prospective study on time trends and return-to-play rates reveals only 65% of players still play at the top level 3 years after ACL rupture - Walden, M.; Hägglund, M.; Magnusson, H.; Ekstrand, J. (British Journal of Sports Medicine, 2016)
Background: Studies investigating the development of ACL injuries over time in football are scarce and more data on what happens before and after return to play (RTP) are needed. Aim: To investigate (1) time trends in ACL injury rates, (2) complication rates before return to match play following ACL reconstruction, and (3) the influence of ACL injury on the subsequent playing career in male professional football players. Methods: 78 clubs were followed between 2001 and 2015. Time trend in ACL injury rate was analysed using linear regression. ACL-injured players were monitored until RTP and tracked for 3 years after RTP. Results: We recorded 157 ACL injuries, 140 total and 17 partial ruptures, with a non-significant average annual increase in the ACL injury rate by 6% (R2=0.13, b=0.059, 95% CI -0.04 to 0.15, p=0.20). The match ACL injury rate was 20-fold higher than the training injury rate (0.340 vs 0.017 per 1000 h). 138 players (98.6%) with a total rupture underwent ACL reconstruction; all 134 players with RTP data (4 players still under rehabilitation) were able to return to training, but 9 of them (6.7%) suffered complications before their first match appearance (5 reruptures and 4 other knee surgeries). The median layoff after ACL reconstruction was 6.6 months to training and 7.4 months to match play. We report 3-year follow-up data for 106 players in total; 91 players (85.8%) were still playing football and 60 of 93 players (65%) with ACL reconstruction for a total rupture played at the same level. Conclusions: The ACL injury rate has not declined during the 2000s and the rerupture rate before return to match play was 4%. The RTP rate within a year after ACL reconstruction was very high, but only two-thirds competed at the highest level 3 years later.